2018
DOI: 10.3390/ijms19030660
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Blockade of Brain Endothelin Receptor Type-A (ETA) Reduces Blood Pressure and Prevents Catecholaminergic Overactivity in the Right Olfactory Bulb of DOCA-Salt Hypertensive Rats

Abstract: Overactivity of the sympathetic nervous system and central endothelins (ETs) are involved in the development of hypertension. Besides the well-known brain structures involved in the regulation of blood pressure like the hypothalamus or locus coeruleus, evidence suggests that the olfactory bulb (OB) also modulates cardiovascular function. In the present study, we evaluated the interaction between the endothelinergic and catecholaminergic systems in the OB of deoxycorticosterone acetate (DOCA)-salt hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
(149 reference statements)
2
5
0
1
Order By: Relevance
“…The increased sympathetic tone found in DOCA-salt rats may be mediated by renal and central sympathetic mechanisms. 27,28 In the present study, the isolated mesenteric vascular bed without the kidney was used; therefore, data from the DOCA-salt group aligned with the results of previous studies. We implied that the elevation in the systemic blood pressure found in DOCA-salt rats is due to hypervolaemia and subsequent increased sympathetic tone.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The increased sympathetic tone found in DOCA-salt rats may be mediated by renal and central sympathetic mechanisms. 27,28 In the present study, the isolated mesenteric vascular bed without the kidney was used; therefore, data from the DOCA-salt group aligned with the results of previous studies. We implied that the elevation in the systemic blood pressure found in DOCA-salt rats is due to hypervolaemia and subsequent increased sympathetic tone.…”
Section: Discussionsupporting
confidence: 77%
“…Research suggests that the increase in sympathetic nerve excitation and the increased responsiveness of the vascular α 1 adrenergic receptor were associated with vascular constriction in the aorta or veins in DOCA‐salt rats. The increased sympathetic tone found in DOCA‐salt rats may be mediated by renal and central sympathetic mechanisms . In the present study, the isolated mesenteric vascular bed without the kidney was used; therefore, data from the DOCA‐salt group aligned with the results of previous studies.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, the hypothesis of this study was that in vivo treatment with NaHS in a chronic model of hypertension may cause reduction of systolic blood pressure. To test this hypothesis, a well-established model of chronic hypertension, DOCA-Salt nephrectomy model, [5,19,36,37] was applied and the results showed that the model caused a significant and persistent elevation of systolic blood pressure. In addition, NaHS was given as an H 2 S donor [38] to hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the pathogenesis of hypertension involves multiple dysregulations of the controlling mechanisms. Overactivation of the sympathetic nervous system, [3] oversecretion of vasoconstrictor hormones and peptides such as angiotensin II and endothelin [4,5], impairment of renal excretory functions [6] in addition to endothelial dysfunction [7,8] represent major pathways implicated in the development of hypertension. Moreover, increased oxidative stress, a hallmark of hypertension, [9] was found to contribute in the development of the previously mentioned pathophysiologic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Hayvanlara sürekli olarak tuzlu içme suyu verilmiştir. DOCA enjeksiyonu ise haftada iki gün uygulanmıştır 14,15 .…”
Section: Introductionunclassified